Kajian Nilai-Nilai Pancasila Di Sektor Perbankan: Peningkatan Peran Perbankan Dalam Pemerataan Sebagai Wujud Dari Keadilan Sosial di Perekonomian Indonesia - Chalid Husen; David Kaluge; Yogi Pasca Pratama (EP FEB UNS, 2015)
This study aims to determine the role of Pancasila values in the banking sector in order to achieve social justice in the form of equity, both of which are applied in the UU pokok perbankan and UU pokok Bank Indonesia, as well as in the level of banking operations. The approach used in this study is a descriptive study using literature review as a kind of research. From the results of literature review found that the UU pokok perbankan and UU pokok Bank Indonesia, which is used by the Indonesian banking industry does not yet reflect the values contained in Pancasila, so that the operational phase toward social justice in the banking sector there is no jurisdiction foundation and the leveling process that became national banking purpose is released to the market mechanism. Keywords: Pancasila, the national banks, Bank Indonesia, UU Pokok Perbankan, UU Pokok Bank IndonesiaJEL: Z13, Z